Multi-electron transfer enabled by topotactic reaction in magnetite - Wei Zhang (Nature Portfolio, 2019)
In contrast to the conventional wisdom on conversion-driven structural collapse of the host, this work shows that lithium conversion in magnetite resembles the intercalation process, going via topotactic reactions, thereby enabling multi-electron transfer and high reversible capacity.